Islamic Law and Peace: Conflict Prevention Among Suku Anak Dalam in Jambi - Al Mubarok, Muhammad Sa'id (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
This article explores methods of proselytization directed at the Suku Anak Dalam (SAD), an indigenous ethnic group residing in Bukit Dua Belas, Jambi, Indonesia, by employing principles of conflict prevention. The study adopts the concept of maqasid al-syariah as a moderate approach tailored to the unique characteristics of the Suku Anak Dalam tribe. The research methodology is literature-based, serving as the primary source of data collection. The findings highlight two significant points. First, the Suku Anak Dalam tribe firmly holds their beliefs and traditions as the foundation of their way of life, making community development and empowerment challenging but feasible. This is demonstrated by several individuals from the tribe who have attained education and embraced Islam. Second, conflicts involving Suku Anak Dalam tribes and surrounding communities predominantly center on agrarian disputes, although the potential for interfaith conflicts cannot be entirely dismissed. Conflict prevention strategies grounded in the maqasid al-syariah framework developed by Muhammad Thahir bin ‘Ashur and Jasser Auda are crucial to addressing these issues. This approach fosters peace, harmony, and coexistence among diverse religious communities. The study recommends cultivating Maqasid al-Shariah values as a foundation for peacebuilding and conflict mitigation in interfaith contexts.